Al-Qaeda Di Semenanjung Arab Dan Kesannya Kepada Ketidakstabilan Geopolitik Di Republik Yaman: Al-Qaeda in The Arabian Peninsula and Its Impact on Geopolitical Instability in The Republic of Yemen - Abdul Hamid, Muhammad Afifi; Abdul Rahman, Mohamad Zaidi; Raja Sulong, Raja Hisyamudin (Online Journal of Research in Islamic Studies, 2023)
A branch of the Al-Qaeda armed terrorist organisation, Al-Qaeda in the Arabian Peninsula (AQAP) was founded by Osama bin Laden to fight the Soviet Union during the Afghan War. This group persisted in opposing Islamic authorities who were viewed as corrupt because of their alliance with Western nations like the United States after the Soviet Union left Afghanistan in 1989. From 2009 to the present, the Republic of Yemen has seen chaos and violence brought on by AQAP, which is led by Nasir al-Wuhayshi. One of the factors causing Yemen's geopolitical instability is AQAP's resistance. This article examines AQAP's role and how it affects Yemen's geopolitical instability. Data collection and data analysis are the two main methods that were used. In this study, documentation approaches were used to obtain any relevant data. The thematic analysis was utilised to analyse the data. As a conclusion, the study's findings support the role of AQAP as one of the factors causing geopolitical instability in Yemen. This finding is notable when compared to research done by other academics and based on the information provided.